Predictors of intention to apply for the excellent teacher position and the moderating role of gender among teachers in Malaysia - Janis, Salina (2019)
Excellent Teacher position is one of Malaysian teachers’ position in their career path within the teaching services promotion system. Recently researchers identified a gap between studies in determining factors of intention and the role of gender of Malaysian teachers applying for Excellent Teacher position. This study examined the predictors of behavior intention in applying for promotion for Excellent Teacher position in Malaysia, and the moderating role of gender in the relationship between the predictors and the intention to apply for the promotion. The objective of the study is to examine the behavioral beliefs (attitude), normative beliefs (subjective norm), and career decision-making self-efficacious beliefs as factors that explain the intention to pursue a promotion to an Excellent Teacher position. The framework of this study was based on the Theory of Planned Behavior by Ajzen (1991). A correlational study design was employed to determine the relationship between the predictors and intention to apply for promotion. This study explores four predictor variables namely, attitude, expectation of others on applying for promotion, career decision making self-efficacy and belief towards performance appraisal system for promotion application for the Excellent Teacher position. Career decision making self-efficacy concept serves as the intrinsic belief factor while belief towards performance appraisal system serves as the extrinsic belief factor that might influence the teachers’ intention to apply for promotion. A self-administered questionnaire was developed and pre-tested for reliability and validity of the questionnaire items. The reliability of the measuring scale was acceptable (ɑ = 0.7). A total number of 500 respondents consisting of 226 males and 274 female teachers who were qualified to apply for promotion. A simple random sampling was conducted by utilizing a zone matrix of school locations (zones: east, west, central, north and south of Peninsular Malaysia, and Sabah and Sarawak). The sample represents a population of school teachers nationwide. Using structural equation modelling (SEM), this study found that expectation of others towards applying for promotion was significantly related to intention to apply for promotion to Excellent Teacher position. Belief towards performance appraisal system for promotion application, attitude towards applying for promotion and career decision making self-efficacy were not significantly related. This study compares the results between gender and found that the effect of belief towards performance appraisal system for promotion application on intention to apply for promotion was moderated by gender. The factor of belief towards performance appraisal system in applying for promotion for the Excellent Teacher position significantly affects intention to apply for promotion among male but not female teachers. The result shows that subjective norm and the external belief of performance appraisal system for promotion as the components of the theory of planned behavior, as well as gender play important roles in predicting teacher’s intention to apply for promotion. This study concludes teachers’ belief towards the performance appraisal system cannot be the predicting factor that contribute towards intention of qualified teachers to apply for the Excellent Teacher positions. It is also concluded that male and female teachers are not affected by the consequences related to applying for promotion for the Excellent Teacher position and their belief towards the performance appraisal system used. As a concluding remark, this study could not support nor strengthen the finding of previous research with regards to belief towards career decision-making self-efficacy. However, the intention to apply for promotion will increase if the expectation of others towards qualified candidates applying for promotion for the Excellent Teacher position also increases. Hence, the process of application for promotion towards Excellent Teacher positions are therefore expected to be more informed of the factors of gender and belief towards others to apply for the promotion application. Further research is recommended to minimize the number of items from variables selected in investigating the relationship between the variables to achieve the model fit for the study. Furthermore, TPB framework can be used to investigate the specific factors that are of concern in a career development studies, particularly on examining the intention of applying for a promotion for the Excellent Teacher position in Malaysia.